Application of Microwave-Assisted Drying to Shorten Granules Drying Process for the Preparation of Thunbergia laurifolia Lindl. Leaf Tablets - Suksaeree, Jirapornchai; Monton, Chaowalit; Chankana, Natawat; Charoenchai, Laksana (Trends in Sciences, 2023)
Thunbergia laurifolia Lindl. is a medicinal plant that belongs to the family of Acanthaceae. It possesses several biological and pharmacological activities. According to the Thai National List of Essential Medicines, T. laurifolia leaves are used for the treatment of fever. This work sought to optimize microwave-assisted drying of Thunbergia laurifolia Lindl. leaf granules to shorten the granule drying process by the 32 full factorial design. Power was varied from 300, 450 and 600 W for 5, 10 and 15 min, to minimize moisture content and maximize rosmarinic acid content. Results showed that the optimal microwave-assisted drying condition within the design space and control space was the power of 450 W for 13 min. This condition gave the moisture content of 4.77 ± 0.24 % and rosmarinic acid content of 0.0566 ± 0.0075 %. The HPLC method was validated; it showed good linearity, specificity, precision, and accuracy. Furthermore, the system suitability was achieved. The T. laurifolia leaf granules obtained from the optimal microwave-assisted drying condition were further used to prepare T. laurifolia leaf tablets by the wet granulation method. Three batches of 650 mg tablets containing 250 mg of T. laurifolia leaf powder were prepared using different compression forces: 500, 1,000 and 1,500 psi. The suitable compression force was 1,500 psi; the tablet formulation had suitable hardness (9.88 ± 0.52 kP), low friability (0.20 %), and a short disintegration time (23.17 ± 0.76 s). Rosmarinic acid marker was dissolved from the tablets for approximately 75 % within 4 h when 0.5 % sodium lauryl sulfate aqueous solution was used as dissolution medium. In conclusion, microwave-assisted drying could be applied in preparing T. laurifolia leaf tablets by shortening the granules drying time. HIGHLIGHTS The 32 full factorial design was applied to optimize microwave-assisted drying of Thunbergia laurifolia leaf granules The optimal microwave-assisted drying condition providing the low moisture content with high rosmarinic acid content was the power of 450 W for 13 min The tablets prepared from laurifolia leaf granules had suitable hardness, low friability, short disintegration time, and a high percentage of rosmarinic acid marker dissolved GRAPHICAL ABSTRACT